Resistance to rice root-knot nematode Meloidogyne graminicola identified in Oryza longistaminata and O. glaberrima - Soriano, Imelda R.; Schmit, Veronique; Brar, Darshan S.; Prot, Jean-Claude; Reversat, Georges (Brill, 1999)
Accessions of Oryza longistaminata and O. glaberrima, two rice species from Africa, and O. sativa were screened to identify sources of resistance to Meloidogyne graminicola. An initial population of 6000 J2/plant was inoculated to cuttings of the African rice species and 5-day-old seedlings of O. sativa. Root nematode densities were estimated 60 days after the last inoculation. O. sativa entries were all susceptible to the rice root-knot nematode. One accession of O. longistaminata represented by two individuals (WL02-2 and WL02-15) and three accessions of O. glaberrima (TOG7235, TOG5674 and TOG5675) were resistant to M. graminicola. DL01-1, an O. longistaminata accession, was susceptible to the rice root-knot nematode. Identification de sources de resistance a Meloidogyne graminicola chez Oryza longistaminata et O. glaberrima - Plusieurs accessions d'Oryza longistaminata et d'O. glaberrima, deux riz africains, et d'O. sativa ont ete criblees pour trouver des sources de resistance a Meloidogyne graminicola. Des inoculums de 6000 J2 par plante ont ete inocules sur des boutures des deux riz africains et sur des plantules de 5 jours d'O. sativa. Les populations presentes dans les racines ont ete evaluees 60 jours apres l'inoculation. Toutes les varietes testees d'O. sativa etaient sensibles. Une accession d'O. longistaminata, representee par deux individus (WLO2-2 et WLO2-15), et trois accessions d'O. glaberrima (TOG7235, TOG5674 et TOG5675) etaient resistantes.